Crown morphometry for Quercus crassifolia Humb. & Bonpl. and Quercus rugosa Née in Hidalgo, Mexico - Hernández-Ramos, Jonathan; Ángeles-Pérez, Gregorio; Pérez-Miranda, Ramiro; Reyes-Hernández, Valentín José; Razo-Zarate, Ramón (Ciência Florestal, 2022)
Quercus crassifolia and Quercus rugosa are species of ecological and economic importance due to their geographical distribution, altitudinal range, abundance in mountainous regions, and plasticity. However, forest management and exploitation have proven incompatible with the ecological needs of each Quercus species, partly due to the lack of quantitative silvicultural tools. For this reason, the following objectives were established i) to determine the morphometric indices (MI) and their correlation with the normal diameter (dn), total height (At), crown diameter (dc) and clean stem height (Afl); and ii) to adjust with Mixed Effects Models (MEM), the characteristics of the Quercus crassifolia and Quercus rugosa crown as a function of dn, with the inclusion of the altitude covariate. With dasometric information from 128 sampling sites distributed in 32 clusters in temperate climate forests of the state of Hidalgo, eight MI were calculated and correlated using the Pearson coefficient. In addition, the Schumacher, Allometric and Linear models were adjusted with MEM to estimate the dc, crown projection area (Apc), and crown proportion in percentage (pc%), respectively. For Quercus crassifolia, for every meter that the crown radius grows there is an increase of 8.8 cm in dn, while in Quercus rugosa the increase is 9.8 cm. The average slenderness index is 0.53 and 0.51, respectively. The Pearson correlation between dasometric variables and MI with the cup shape was -0.61 and for the total height, Apc, dc and pc% with the dn it was >0.64, both for the two species. The MEMs were statistically robust and without violations of the regression assumptions. The silvicultural information generated can be a reference to plan management and monitoring activities in the Quercus crassifolia and Quercus rugosa stands.